Blue Carbon Dynamics in the Sundarban Biosphere Reserve (SBR): Impacts of Climate and Anthropogenic Factors - Gayen, Manotosh (Surviving Sundarbans: Tragedy and Hope, Edition 1, 2025)
The Sundarban Biosphere Reserve (SBR) in India, known as the world's largest mangrove forest, is a key player in global carbon cycling and other biogeochemical processes, serving as a significant blue carbon ecosystem. Blue carbon pertains to the carbon captured by marine and coastal ecosystems, especially mangroves, seagrasses, and salt marshes. Although various assessments of carbon stock and flux have been conducted over the past decades, there is still a lack of concrete understanding regarding carbon source and sink patterns, particularly in the biodiversity-rich Sundarbans, which encompasses a 10,000 km² mangrove area. To identify research gaps in mangrove blue carbon in this region, a recent decade-long inventory of carbon stock pools (including aboveground, belowground, and soil) and factors affecting carbon mass balance (such as cyclones, salinity, sea level rise, temperature, precipitation, and water-air CO2 flux) was summarized. This review emphasizes carbon sequestration, storage in vegetation and soil, and the influence of anthropogenic and climatic factors. Gaining insight into these dynamics is crucial for developing effective conservation strategies and enhancing the SBR's role in mitigating climate change.